2015
DOI: 10.1155/2015/143832
|View full text |Cite
|
Sign up to set email alerts
|

Ciprofloxacin-Induced Thrombotic Thrombocytopenic Purpura: A Case of Successful Treatment and Review of the Literature

Abstract: A 49-year-old African American woman was admitted to our hospital with abdominal pain, nausea, vomiting, lethargy, and confusion. She was receiving ciprofloxacin for a urinary-tract infection prior to admission. Laboratory examination revealed anemia, thrombocytopenia, elevated lactate dehydrogenase, and serum creatinine. Peripheral smear showed numerous schistocytes, and the patient was diagnosed with thrombotic thrombocytopenic purpura (TTP). Ciprofloxacin was identified as the offending agent. The patient r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Although it is possible that this patient could have had secondary TTP from oral clindamycin therapy, a literature search failed to demonstrate clindamycin-induced TTP. There have been 2 cases reported of clarithromycin-induced TTP [ 12 ]. Ciprofloxacin has been associated with TTP but our patient was treated with topical ciprofloxacin drops only [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although it is possible that this patient could have had secondary TTP from oral clindamycin therapy, a literature search failed to demonstrate clindamycin-induced TTP. There have been 2 cases reported of clarithromycin-induced TTP [ 12 ]. Ciprofloxacin has been associated with TTP but our patient was treated with topical ciprofloxacin drops only [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The impairment in kidney function markers following ciprofloxacin administration had been documented in Hafiz et al [32] who mentioned that ciprofloxacin treatment was an offending agent causing an increase in serum lactate dehydrogenase and serum creatinine among other adverse effects. Moreover, Shaki et al, [33] reported that ciprofloxacin showed an oxidative damage and inflammation with marked nephrotoxicity, represented by increase in serum BUN and creatinine with histopathological changes.…”
Section: Levofloxacinmentioning
confidence: 94%
“…Acquired TTP is usually caused by autoantibodies that either inhibit or clear ADAMTS13. Although ciprofloxacin has been reported as a potential cause of drug‐induced TTP, 11 it was continued in our patient, as the temporal onset of thrombocytopenia seemed too soon to implicate it as a biologically plausible trigger. Further, ciprofloxacin was not listed in a systematic review of drug‐induced TTP 12 …”
Section: Case Presentationmentioning
confidence: 85%